An overview of the (eco)toxicological effects of flame retardants emerging in water and sediment - Dowbysz, Adriana M.; Samsonowicz, Mariola; Kukfisz, Bożena (Journal of Water and Land Development, 2023)
Flame retardants (FRs) that have an adverse effect on human and the environment have been subject to regulation since 1972. However, FRs emerging as a replacement, are not proving to be fully environmentally safe. Water and sediment contamination by FRs, including organophosphorus (OPFRs) and novel brominated (NBFRs) ones, is a matter of major concern. Due to their common usage, many release sources, and relatively high mobility, they pose a threat to aquatic organisms and ecosystems. This review summarises studies on the OPFRs’, and NBFRs’ simultaneous occurrence in water and corresponding sediment. The main sources of occurrence and routes of entry of FRs into the environment are presented. The newest reports on the ecotoxicity of selected FRs had been summarised in order to bring the matter to attention. The research revealed that although great efforts had been made to study the occurrence of OPFRs and NBFRs in water and sediment separately, there is a lack of research on their occurrence in both media in the same area. Although major efforts have been made to study the ecotoxicity of OPFRs, there are some deficiencies for the NBFRs. Considering their relatively high ecotoxicity, further studies should be conducted on joint ecotoxicity, which may cause synergistic or antagonistic effects.
Keywords: organophosphorus flame retardants; novel brominated flame retardants; ecotoxicity; water; sediment